2022
DOI: 10.1007/s12020-022-03020-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of adrenal venous sampling (AVS) in primary bilateral macronodular adrenocortical hyperplasia (PBMAH): a study of 16 patients

Abstract: Objective Primary bilateral macronodular adrenocortical hyperplasia (PBMAH) is a rare cause of ACTH-independent Cushing’s syndrome. Current guidelines recommend bilateral adrenalectomy for PBMAH, but several studies showed clinical effectiveness of unilateral adrenalectomy despite bilateral disease in selected patients. Our aim was to evaluate the gain of information which can be obtained through adrenal venous sampling (AVS) based cortisol lateralization ratios for guidance of unilateral adrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…AVS was performed to identify a hormonally dominant side of cortisol production to guide unilateral adrenalectomy. Most of these patients (patients 1 to 12, patient 17 and patient 18) were already part of our study on the clinical role of AVS in PBMAH ( 14 ). As described also in that publication, patients underwent biochemical screening for Cushing’s syndrome by the three recommended screening tests: 1-mg dexamethasone suppression test (LDDST), late-night salivary cortisol (LNSLC) and 24h urinary free cortisol (UFC), all performed using immunoassay.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…AVS was performed to identify a hormonally dominant side of cortisol production to guide unilateral adrenalectomy. Most of these patients (patients 1 to 12, patient 17 and patient 18) were already part of our study on the clinical role of AVS in PBMAH ( 14 ). As described also in that publication, patients underwent biochemical screening for Cushing’s syndrome by the three recommended screening tests: 1-mg dexamethasone suppression test (LDDST), late-night salivary cortisol (LNSLC) and 24h urinary free cortisol (UFC), all performed using immunoassay.…”
Section: Methodsmentioning
confidence: 99%
“…Germline ARMC5 (armadillo repeat containing 5) sequencing was performed in 15 patients. Inactivating mutations of ARMC5 , a putative tumor-suppressor gene, are associated with a more severe hypercortisolism, bigger adrenals with a higher number of nodules ( 15 ).The assays for the screening tests, baseline ACTH and ARMC5 status were described in the online Supplementary Material ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reviewed 16 patients with PBMAH: 11 with CS and 5 with incidental detection of adrenal masses. 23 In their study, they concluded that the use of AVS in the context of CS due to PBMAH with marked asymmetry of the adrenal glands is limited. Unlike our study, lateralization toward the smaller adrenal gland was not seen in any of these patients.…”
Section: Posthoc Diagnostic Accuracy Avs Cutoff Valuesmentioning
confidence: 99%